The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/mpa.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Fat Accumulation, Fibrosis, and Acinar Cell Injury in the Zucker Diabetic Fatty Rat Fed a Chronic High-Fat Diet

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 51 publications
4
44
0
1
Order By: Relevance
“…In the present study, histological examination of pancreatic acinar cells in HFD-induced obese rats revealed marked accumulation of fat droplets, indicating ectopic fat deposition in the pancreas. Similar results were found in animal models of metabolic syndrome [24,25]. In parallel, HFD-fed rats also showed a marked increase in TG levels in the pancreas along with up-regulated SREBP-1c expression.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, histological examination of pancreatic acinar cells in HFD-induced obese rats revealed marked accumulation of fat droplets, indicating ectopic fat deposition in the pancreas. Similar results were found in animal models of metabolic syndrome [24,25]. In parallel, HFD-fed rats also showed a marked increase in TG levels in the pancreas along with up-regulated SREBP-1c expression.…”
Section: Discussionsupporting
confidence: 73%
“…We recently demonstrated that intra-lobular fat accumulates in exocrine pancreatic tissue and that lipid droplets in acinar cells increase in Zucker diabetic fatty rats, which is an animal model of type 2 diabetes caused by the chronic intake of a high-fat diet. These conditions appear cause acinar cell injury and fibrosis[21]. Thus, additional clinical and experimental studies of the interrelationships between diabetes, metabolic syndrome and pancreatic injury should be conducted to clarify the pathogenesis of “non-alcoholic fatty pancreatic disease”.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, adipocytes in WAT abundantly express the angiotensin II type-1 receptor (AT1) (23, 24), a major pro-fibrotic pathway that becomes activated in a pro-inflammatory environment (23, 24). Obesity also leads to fat accumulation in the normal pancreas (steatosis), which generates a similar inflammatory process within the pancreas itself, with increased expression of cytokines, extracellular matrix remodeling, and fibrosis (7, 25, 26). Importantly, cancer lesions in obese mice and patients have an increased adipocyte content (27, 28).…”
Section: Introductionmentioning
confidence: 99%